PENGARUH EFIKASI DIRI, GAYA BELAJAR, KEBIASAAN BELAJAR, TEMAN SEBAYA, DAN LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR SISWA KELAS X PADA MATA PELAJARAN EKONOMI DI SMAN 1 KAPUR IX: Penelitian Deskriptif - Ade Silvia; Vivina Eprillison; Stevani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The results of this research show that 1) there is a significant influence between self-efficacy (X1) on the learning achievement of class The coefficient value is -0.045 with a calculated t value < t table (-0.445 < 1.66792) and a significant value of 0.657 > 0.05, 3) There is a significant influence between study habits (X3) on the learning achievement of class 0.048 < 0.05, 4) There is a significant influence between peers (X4) on the learning achievement of class 1 Lime IX, with a coefficient value of 0.179 with a calculated t value > t table (2.728 > 1.66792) and a significant value of 0.088 < 0.05. 6) the variables of self-efficacy, learning style, study habits, peers and family environment together (simultaneously) have a significant effect on learning achievement with a calculated F value of 5.519 > F table of 2.31 and a significant value of 0.000 < 0.05.